The Discovery of Familia Adenomatous Polyposis in Patients With Intestinal Malrotations : A Rare Case - Ritonga, Nisa Alyananda; Hermanto, Hermanto; Akbar, Muhammad Khalilul; Nurmasithah, Nurmasithah; Rumondang, Sonia Edna (Journal Research of Social Science, Economics, and Management, 2025)
Polyps are masses that project into the gastrointestinal tract, common in childhood, affecting about 1% of preschool and school-age children. They are the leading cause of rectal bleeding in children aged 2 to 5. Adenomatous polyps, found in less than 3% of children with polyps, are often discovered incidentally. In this case, they were found alongside midgut malrotation volvulus, diagnosed late. An 8-year-old boy presented with worsening abdominal pain over the last month, which was intermittent and position-dependent. The pain was accompanied by explosive diarrhea, bloating, and a sensation of water moving in the abdomen when changing position. He also experienced daily vomiting, nausea, and a decrease in appetite. During treatment evaluation, midgut malrotation volvulus was detected along with familial adenomatous polyposis in the small intestine and colon. Early detection could have improved the prognosis, which is better when identified sooner. Once histopathology results are available, it will be determined if chemoprevention is necessary or if regular check-ups are sufficient.